Vocational qualifications and progression to higher education: the case of the 14-19 Diplomas in the English system - Hodgson, Ann [Verfasser]; Spours, Ken [Verfasser] (My University, 2010)
"Ensuring effective progression from vocational qualifications to higher education has become an important issue internationally as a part of government strategies to raise skill levels and to provide more equitable access to tertiary level study. From September 2008, the Government in England has begun to introduce a new set of qualifications for 14-19-year-olds, called Diplomas, intended to prepare young people for both employment and higher education. In competition with the traditional General Certificate of Education Advanced Levels, the reputation of the Diploma will depend on its ability to provide a progression route to university. Drawing on evidence from a variety of sources, including five seminars involving further education teachers, higher education admissions tutors and representatives of national agencies, this article suggests that the potential of the Diplomas to become a major route to higher education will be constrained by what we term a 'low uptake, low understanding, low recognition and high complexity syndrome'. Using historical sources, the article also points to key similarities between the new Diplomas and the earlier, ill-fated Advanced General National Vocational Qualifications as middle track awards in the English triple-track qualifications system. We conclude by suggesting two contrasting possible strategies to address this issue." (Autorenreferat, BIBB-Doku)
Keywords: G 2.5.3 Anschlussfähigkeit von Bildungsgängen; S 1.3 Berufliche Erstausbildung; S 1.4 Hochschulbildung; I 2.2.1 Westeuropa; Durchlässigkeit im Bildungssystem; Berufsbildung; Hochschulbildung; Berufliche Qualifikation; Hochschulzugang; England